Procesos de la ciencia y desarrollo cognitivo en Bachillerato - Palacios, C.; López, F.; Garrote Flores, R.; Montes, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The study described in this report was designed to investigate the relationship between integrated process skills and formal thinking in high school students. Paper and pencil measurement of both variables was made using a sample of 189 students, the average age being, 15 years. The resulting correlation showed a Pearson's of 0.68. An empirical analysis of the cognitive demand of different science process skills was carried out. Some implications for Science Education are, finally, discussed.